1993
DOI: 10.1088/0963-0252/2/4/007
|View full text |Cite
|
Sign up to set email alerts
|

Capacitive RF discharges modelled by particle-in-cell Monte Carlo simulation. II. Comparisons with laboratory measurements of electron energy distribution functions

Abstract: Bi-Maxwellian electron energy distribution functions (EEOFS) have been measured experimentally in argon RF discharges at 13.56 MHz by Godyak et a/ (Plasma Sources Sci. Techno/. 1 36 (1992)). The observed EEDFS at low pressures had very-low-energy and high-energy components. We show particle-incell Montecarlo (PICMCC) simulations, which produce the same EEDFS. Excellent agreement is obtained between the effective low and high electron temperatures in simulations and those measured in the laboratory. Our simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
57
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(66 citation statements)
references
References 21 publications
8
57
1
Order By: Relevance
“…The proposal made in [31] was that electron-electron collisions between the cold and hot electrons is the dominant heating mechanism for low-energy electrons. However, there are a number of particle simulation studies [32][33][34], including one by the present author, that show reasonable agreement with this or similar experiments without including electron-electron collisions, and a larger number of studies of related problems, e.g., [35][36][37][38][39][40][41][42], also neglecting electron-electron collisions. In this section, we re-examine these simulation results, with special attention to convergence with respect to N D .…”
Section: A Radio Frequency Discharge In Argonsupporting
confidence: 69%
“…The proposal made in [31] was that electron-electron collisions between the cold and hot electrons is the dominant heating mechanism for low-energy electrons. However, there are a number of particle simulation studies [32][33][34], including one by the present author, that show reasonable agreement with this or similar experiments without including electron-electron collisions, and a larger number of studies of related problems, e.g., [35][36][37][38][39][40][41][42], also neglecting electron-electron collisions. In this section, we re-examine these simulation results, with special attention to convergence with respect to N D .…”
Section: A Radio Frequency Discharge In Argonsupporting
confidence: 69%
“…The phenomenon of stochastic heating at low pressures, leading to bi-Maxwelian electron energy distribution functions was discovered experimentally by Godyak [20]. This was first confirmed by PIC MCC simulations of Vahedi et al [10]. In [21] PIC simulation was applied to evaluate the analytical models for stochastic heating rate from [1] and [22] and finally to derive an improved formulation, which was then extended for the case of the dual frequency discharges.…”
Section: Introductionmentioning
confidence: 89%
“…In this parameter regime, the electron energy distribution function substantially deviates from a simple Maxwellian. Experiments 29,30 and particle-in-cell (PIC) simulations 31 have shown that the electron energy distribution is a BiMaxwellian that arises from the stochastic heating mechanism in a Ramsauer gas. This aspect must also be taken into account in a charging model for dust in the sheath of an rf discharge.…”
Section: Introductionmentioning
confidence: 99%